Sistem Pendukung Keputusan Pemilihan Guru Berprestasi Di Kecamatan Kradenan Kabupaten Grobogan Menggunakan Metode Simple Additive Weighting - Atika, Fara; , Prof. Budi Murtiyasa, M. Kom (2017)
Teacher is one of models in education world who is playing roles as educator, counselor, and evaluator and as example for his or her students. Predicate of good performed teacher is one of the ways to improve quality of education in Kecamatan Kradenan, Grobogan Regency. The existence of many teachers made difficulty in making selection of good teachers immediately and accurately and the selection consumed great time to calculate it. Purpose of the research is to make Decision Support System (DSS) with web-based Simple Additive Weighting (SAW) method that is designed by using Php Hypertext Preprocessing (PHP) and MySQL database to facilitate selection of good teachers accurately and immediately without consuming great time for calculation. In addition, the system can be accessed everywhere and anytime because it is a web-based method and connected directly to internet network. Selection of good teachers is made by summing results of appraisals on existing criteria with predetermined weight. The results will be ranked according to calculation contained in SAW method.